On Recent Developments in Biosynthesis and Application of Au and Ag Nanoparticles from Biological Systems - Ashutosh Kumar Verma; P. Kumar (Journal of Nanotechnology)
Gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs) are extensively studied nanoparticles (NPs) and are known to have profound applications in medicine. The researcher made continuous efforts for the environmental-friendly and economical methods, such as biogenic methods known as green synthesis. There are many strategies for separating and applying gold (Au) and silver (Ag) nanoparticles, of which biological routes have emerged as efficient, low-cost, and environmentally friendly techniques. This review focuses on recent developments of green synthesized AuNPs and AgNPs using biogenic sources such as algae, animals, plants, microbes, bacteria, fungi, and so on. Hence, it discusses their numerous biomedical applications and separating Au and Ag nanoparticles from plants, bacteria, fungi, and algae.